The different effects of gonadotropin-releasing hormone agonist therapy on body mass index and growth between normal-weight and overweight girls with central precocious puberty - Yang, Won Jun; Ko, Keun Hyeok; Lee, Kon Hee; Hwang, Il Tae; Oh, Yeon Joung (Annals of pediatric endocrinology & metabolism, 2017)
The effects of gonadotropin-releasing hormone agonist (GnRHa) treatment on body mass index (BMI) are controversial in girls with central precocious puberty (CPP). We therefore evaluated auxological parameters during GnRHa therapy in patients with CPP, specifically focusing on changes in BMI. Seventy-seven girls with idiopathic CPP who underwent GnRHa therapy were retrospectively recruited. We investigated BMI changes during the treatment period after stratifying them according to baseline BMI status as follows: normal (BMI percentile of <85th) and overweight groups (BMI percentile of ≥85th). The incidence of overweight/obesity (40.3%/23.4%) was very high in the girls with CPP. In the overall study population, no significant BMI change was observed during the GnRHa treatment period. However, when stratified according to baseline BMI status, the normal-weight group showed a significant increase in BMI-standard deviation score (SDS), whereas the overweight group showed no change in BMI-SDS. Baseline BMI-SDS was an independent predictor of changes in BMI during the GnRHa treatment period. Changes in weight-SDS were similar, but changes in height-SDS were significantly greater in the overweight group than in the normal-weight group, which explains the observed difference in BMI-SDS. Our results demonstrate that the difference in the pattern of BMI changes among our CPP patients suggests that delayed puberty induced by GnRHa treatment may have different effects on linear growth according to baseline body composition. This study underscores the importance of individualized lifestyle intervention in CPP children.